His bundle pacing. Technical aspects and evidence base for use as an alternative to cardiac resynchronization therapy and conventional electrical pacing - S. N. Krivolapov; M. V. Gorev; Yu. Yu. Gulyaev; M. S. Khlynin; R. E. Batalov (Российский кардиологический журнал, 2025)
His bundle pacing is a direct pacing of the specialized His-Purkinje conduction system with the aim of physiological ventricular activation, in contrast to the dyssynchronous activation by conventional myocardial pacing.In this review article on His-Purkinje conduction system pacing, the authors evaluate the available data and current practice, and assess emerging and future directions in this fast growing area. We analyzed the available publications on His bundle and conduction system pacing.Since the first report of permanent His-bundle pacing (HBP) in 2000, the earliest incarnation of stylet-driven technique has been replaced by the more effective non-stylet-driven approach. Widespread adoption has generated a large evidence base. Single-center observational studies have been complemented by large multicenter international registries, mechanistic studies, and the first randomized controlled trials. New data have clarified the mechanisms of РИЗ and illustrated the nature and extent of its potential benefits in preventing pacing cardiomyopathy and correcting bundle branch block.Conduction system stimulation is the most physiological type of cardiac pacing in patients with a narrow QRS complex. Conduction system pacing may be an effective alternative to biventricular pacing in cardiac resynchronization therapy. Randomized controlled trials are needed to expand the evidence base.